Long‐Term Clinical Outcomes of a Biodegradable Polymer‐Based Biolimus‐Eluting Stent. (1st March 2016) - Im, Eui; Kim, Gwang‐Sil; Shin, Dong‐Ho; Kim, Jung‐Sun; Kim, Byeong‐Keuk; Ko, Young‐Guk; Choi, Donghoon; Jang, Yangsoo; Hong, Myeong‐Ki
Abstract : Objectives: To investigate the long‐term clinical outcomes of biolimus‐eluting stents with biodegradable polymers in real‐world clinical practice. Background: Long‐term clinical outcomes of biolimus‐eluting stents have not been clearly established. Methods: A total of 824 all‐comer patients (971 lesions) treated with unrestricted implantation of a biolimus‐eluting stent with a biodegradable polymer were prospectively enrolled. Patients were divided into complex (413 patients) versus noncomplex (411 patients) groups according to the complexity of coronary lesions. Long‐term clinical outcomes for stent efficacy (target lesion revascularization) and safety (composite of cardiac death, target lesion‐related myocardial infarction, and definite or probable stent thrombosis) were compared between the two groups during 5 years of follow‐up. Results: The complex group showed higher rates of decreased left ventricular ejection fraction, impaired renal function, previous history of myocardial infarction, and diabetes mellitus compared to the noncomplex group. In the overall population, the 5‐year cumulative rate of target lesion revascularization was 4.8% (8.3% in the complex group vs 1.6% in the noncomplex group, P < 0.001). For stent safety, the 5‐year cumulative rate for a composite of cardiac death, target lesion‐related myocardial infarction, and stent thrombosis was 2.5% overall (3.9% in the complex group vs 1.1% in the noncomplex group, P = 0.010). Overall 5‐year cumulative rate of stent thrombosis was 0.4% (0.5% in the complex vs 0.2% in the noncomplex group, P = 0.561) with no very late stent thrombosis (VLST). Conclusions: Biodegradable polymer‐based biolimus‐eluting stents showed favorable efficacy and safety in all‐comer patients during 5 years of follow‐up. (J Interven Cardiol 2016;29:162–167)